Contemporary Da'wah Strategy of the Tabligh Jamaat in Addressing Teen Moral Issues - Anis Mahmud Sitompul; Abdullah Abdullah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the moral issues faced by teenagers and the contemporary preaching strategies of the Tabligh Jamaat in addressing them in Deli Tua District, including identifying the supporting and inhibiting factors in the implementation of preaching. The research uses a qualitative approach with a descriptive method. The study involved six informants selected through purposive sampling, consisting of the leaders and members of the Tabligh Jamaat, two teenagers, and two parents. Data were collected through interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data display, and drawing and verifying conclusions. The validity of the data was tested through source and technique triangulation. Research results show that the moral problems of teenagers in the Deli Tua District are related to excessive use of social media, peer influence, decreased involvement in religious activities, and weak family supervision. The Jamaah Tabligh's preaching strategy is carried out through persuasive approaches, interpersonal communication, preaching by action, jaulah (missionary journeys), ta'lim (religious education), example-setting, and mosque-based guidance at Masjid As-Syakirin. This strategy helps to increase teenagers' involvement in religious activities and gradually encourages the formation of positive behavior. Supporting factors include family support, a conducive mosque environment, member role models, and harmonious social relationships, while inhibiting factors include peer influence, excessive social media use, low youth participation, weak family supervision, and stigma towards Jamaah Tabligh. The research concludes that fostering teen morality requires a preaching strategy that is persuasive, ongoing, community-based, and supported by synergy between the Tabligh community, families, mosques, schools, and society